2012
DOI: 10.1371/journal.pone.0042185
|View full text |Cite|
|
Sign up to set email alerts
|

Identification and Characterization of ZEL-H16 as a Novel Agonist of the Histamine H3 Receptor

Abstract: The histamine H3 receptor (H3R) has been recognized as a promising target for the treatment of various central and peripheral nervous system diseases. In this study, a non-imidazole compound, ZEL-H16, was identified as a novel histamine H3 receptor agonist. ZEL-H16 was found to bind to human H3R with a Ki value of approximately 2.07 nM and 4.36 nM to rat H3R. Further characterization indicated that ZEL-H16 behaved as a partial agonist on the inhibition of forskolin-stimulated cAMP accumulation (the efficacy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 50 publications
5
30
0
Order By: Relevance
“…1F,G). This is consistent with the H3R FRET sensor internalizing upon agonist treatment in a similar way to the wild-type H3R [43].…”
Section: Functional Characterization Of the Intramolecular H3 Receptosupporting
confidence: 85%
“…1F,G). This is consistent with the H3R FRET sensor internalizing upon agonist treatment in a similar way to the wild-type H3R [43].…”
Section: Functional Characterization Of the Intramolecular H3 Receptosupporting
confidence: 85%
“…H 3 receptors could be expressed not only in beta cells but also in these other cell types. H 3 receptor protein was detected in the cytoplasm in addition to the plasma membrane (Figure C,D), suggesting that some of the H 3 receptors are internalized by ligand binding in pancreatic beta cells (Shi et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Our previous data, using a HEK293 cell line stably expressing human H3R, has shown that H3R triggers ERK1/2 phosphorylation in a concentration and time‐dependent manner in response to an agonist (Shi et al . ). Here, we used the same stable HEK293‐H3R cell line and cultured mouse cortical neurons, which endogenously express H3R, to characterize the signaling pathway of H3R‐mediated ERK1/2 activation.…”
Section: Resultsmentioning
confidence: 97%
“…Our own previous study had demonstrated that the partial agonist ZEL‐H16 could activate ERK1/2 signaling pathway and that this effect was almost completely blocked by co‐incubation with thioperamide and PTX (Shi et al . ). In this study, we clearly demonstrate that stimulation of histamine or imetit triggers ERK1/2 phosphorylation in both HEK293 cells and cultured cortical neurons.…”
Section: Discussionmentioning
confidence: 97%